Language and simplexity: A powers view. (January 2019) - Lassiter, Charles
Abstract: The notion of simplexity is that complex problems are often solved by novel combinations of simple mechanisms. These solutions aren't simple; they're simplex. Language use, as a complex behavior, is ripe for simplex analysis. In this paper, I argue that the notion of powers—an organism's capacity to instigate or undergo change—is doubly useful. First, powers, as opposed to mental representations, are a suitable object for simplex analysis. So conceptualizing languaging in terms of powers gets us one step closer to a simplex analysis of language. But thinking of languaging in terms of powers has an additional payoff. Berthoz asserts that the concept of simplexity is related to the concept of meaning. How they're related is unclear. Conceptualizing languaging in terms of powers injects meaningfulness into lived world of the organism. Consequently, the concept of powers can act as a bridge between the concepts of meaningfulness and simplexity.